Rubbish Monitoring System (R-Ms) - Nabila, Mohd Nizam (2023)
The smart rubbish monitoring system is an IoT-based project that can measure the level of rubbish for each bin. With the combination of several hardware devices such as Raspberry Pi and ultrasonic sensors it can further strengthen the system in this project. The main purpose of using the Raspberry Pi is that it is very easy to use and the Wi-Fi connection is continuous. The main reason of smart rubbish monitoring system created is because for the sake of maintaining cleanliness around the faculty and the welfare of users in faculty that use rubbish bins to dispose of rubbish. With the creation of this smart rubbish monitoring system, it can approximately help and facilitate the rubbish pickers to pick up the rubbish in an organized and timely manner. The habitual problem faced is that the amount of garbage that is too much has caused the smell pollution to occur in the rubbish bin area. Therefore, the goal to be achieved is to create a rubbish monitoring system that can manage rubbish in a more organized and effective manner. Ultrasonic sensor will be placed on the top of the rubbish bin to detect the volume of rubbish. If the rubbish in the bin is full, then a notification will be sent to the user via the Blynk application. The language used is C++. The methodology in the prototype is a user- friendly method. Therefore, the creation of this project can help the faculty to maintain a clean and attractive environment and can provide comfort to students and workers.